The effect of increased preset intraocular pressure level on choroidal blood flow during phacoemulsification - Yu. V. Takhtaev; T. N. Kiseleva; R. B. Shliakman (Российский офтальмологический журнал, 2022)
Purpose: to evaluate blood flow velocity in the posterior short ciliary arteries during phacoemulsification (PE) at different levels of intraocular pressure (IOP).Material and methods. The study included 29 patients aged 62–83 (average 71.2 ± 6.0) with initial-stage age-related cataract. PE was performed using the Alcon Centurion vision system at a preset IOP level of 60 mm Hg. Blood flow velocity was determined three times using an expert-class ultrasound scanner (GE Logiq S8): immediately before surgery (before opening the eyeball), intraoperatively at an IOP level of 58.77 ± 8.28 mm Hg, and after surgery and IOP normalization. Additionally, the IOP level was measured three times (by Icare PRO tonometer). The blood pressure level was monitored by the standard method on the brachial artery using the Dr ger Vista 120 system. The measurement results were compared with the control group which included 20 healthy fellow eyes.Results. A decrease in blood flow velocity was established upon reaching the IOP level of 58.77 ± 8.28 mm Hg. The maximum systolic blood flow velocity in the posterior short ciliary lateral artery decreased from 14.46 ± 2.92 to 11.22 ± 2.55 cm/s, while the final diastolic blood flow fell from 5.11 ± 1.83 to 2.97 ± 1.27 cm/s. The maximum systolic blood flow velocity on the medial side also fell from 12.37 ± 2.74 to 9.50 ± 1.68 cm/s, and the final diastolic velocity fell from 4.54 ± 1.35 to 2.73 ± 0.91 cm/s (p < 0.05).Conclusion. During PE, the IOP level exceeding certain values leads to a decrease in blood flow velocity in the posterior short ciliary arteries. It is important to realize, however, that autoregulatory mechanisms for maintaining stable hemodynamics are limited if IOP levels are increased.